Case Report: Distinctive EEG Patterns in SCARB-2 Related Progressive Myoclonus Epilepsy - Hotait, Mostafa; Dirani, Maya; El Halabi, Tarek; Beydoun, Ahmad (Frontiers in Genetics, 2020)
Action myoclonus-renal failure syndrome (AMRF) is a rare, recessively inherited form of progressive myoclonus epilepsy (PME) caused by mutations in the SCARB2 gene and associated with end-stage renal failure. In addition to severe progressive myoclonus, the neurological manifestations of this syndrome are characterized by progressive ataxia and dysarthria with preserved intellectual capacity. Since its original description, an increasing number of “AMRF-like” cases without renal failure have been reported. We describe the case of a 29-year-old woman with progressive disabling myoclonus associated with dysarthria and ataxia who was found to have a novel homozygous frameshift mutation in the SCARB2 gene. In addition, this report emphasizes the presence of two EEG patterns, fixation-off phenomenon and bursts of parasagittal spikes exclusively seen during REM sleep that appear to be characteristic of this condition.